Hesitations in Speech Production in the Media - Zovko Dinković, Irena (Array, 2014)
Nowadays we are witnessing a substantial growth in the number of radio stations, as well as a simultaneous decline in the quality of hosts’ speech, particularly its fluency. Whereas people may be quite tolerant of various hesitations in everyday conversations, listeners often find dysfluencies in the speech of radio hosts distracting and irritating, expecting the hosts to be skilled in controlling their output. This research paper therefore offers a contrastive analysis of hesitations in the speech production of English and Croatian radio hosts, with the aim of determining whether the frequency of hesitation markers can be related to the formal training of hosts. If so, we can suppose that greater fluency of speech may be achieved through practice. To this purpose we have analyzed eight minutes (480 seconds) of speech of 32 radio hosts, 16 American and 16 Croatian, with an equal number of males and females in each group. Also, half of the hosts work on public radio stations, and the other half on commercial ones. In order to obtain as objective results as possible, the analyzed samples were taken from different episodes of talk-shows on various subjects, as well as from different parts of the episodes (beginning, middle part and ending). The results indicate that there is no correlation between gender and fluency since there was no relevant difference in the frequency of hesitations produced by male and female hosts, in spite of the generally accepted popular view that women are more fluent and verbal than men. More importantly, the results indicate that fluency is an aspect of speech that can be improved through practice and formal training. A surprisingly similar number of hesitations in the speech of American and Croatian hosts confirms the fact that speech fluency is a cognitive aspect of language, independent of language specific features.